Agrotourism: Avenue For Rural Areas With Special Reference To Pune Region - et. al., Rahul Shinde, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Over the decades Tourism is fastest growing service sector in India. Alongside tourism sector Agriculture is the main sector of Indian Economy. Near about 65 percentage of the population of India is directly or indirectly dependent of agriculture sector. Total contribution of agriculture sector in total GDP of India was 19.9% for FY 2020-21. Adding new income-generating activities to existing agriculture will undoubtedly boost agriculture's contribution to national GDP. This will be accomplished by agritourism. In the Indian tourism industry, agritourism is the most recent trend from last decade. Today's visitors all want to get away from the hustle and bustle of city life and remain in the quiet world of rural areas abounding with farming activities. Agri tourism provides an opportunity to have a genuine, enchanting, and honest encounter with real life. Looking into the opportunity and people’s interest towards the agrotourism, this paper enlightens the concept of agrotourism, opportunities and future growth in same filed as well as people’s awareness towards the agrotourism. Paper is based on secondary as well as primary data with special reference to Pune region.